Thermo-magnetic properties of Fe2O3-doped lithium zinc silicate glass-ceramics for magnetic applications. Issue 18 (15th September 2021) - Shakdofa, Mohamad M.E.; Mahdy, Ebrahim A.; Abo-Mosallam, H.A.
Abstract: The crystallization behaviour and thermo-magnetic characteristics of glass-ceramic based on the 15Li2 O–20ZnO–10CaO–55SiO2 system doped with varied Fe2 O3 additions (0.0125, 0.025, and 0.05 mol) are described in this work. In some cases, Al2 O3 was also added to the iron-containing sample. Glasses were successfully prepared by melt-quenching technique and converted into glass-ceramics by controlled heat-treatment, using DTA, SEM, XRD, and VSM techniques. The density, thermal expansion coefficients (TCE), and magnetic characteristics of the glass-ceramic were examined. XRD results confirmed characteristic peaks for various phases like quartz, Li2 ZnSiO4, wollastonite, Li2 Si2 O5, ZnFe2 O4, and β-spodumene. By doping Fe2 O3 and Al2 O3 with lowering annealing temperature, the particle size was reduce, resulting in glass-ceramics with a more uniform and dense microstructure. The density of glass-ceramics rises from 2.74 g/cm 3 to 3.45 g/cm 3, whereas the TCE values in average 14–78 × 10 −7 /°C with temperature range of 25–500 °C. The doped glass-ceramics have superior magnetic properties with saturation magnetization (0.143–0.548 emu/g), the coercivity force (65.116–86.359 G), and remanence magnetization (0.074–0.436 emu/g). Under an alternating magnetic field, the presence of the Zn-ferrite phase in the glass-ceramics improves their magnetic properties and increases their heat-generating capability. Certain features of the doped glass-ceramics control the extensive variety of possibilities for their usage in various magnetic applications particularly for cancer hyperthermia treatment.